Effects of exercise-based cardiac rehabilitation on heart rate variability and turbulence in patients with ST elevation myocardial infarction - Zengin, İsmet; Arı, Selma; Arı, Hasan; Melek, Mehmet (The European Research Journal, 2020)
Objectives: The objective of this study was to evaluate the effect of the exercise-based cardiac rehabilitation (CR) on the heart rate variability (HRV) and turbulence (HRT) in patients with ST elevation myocardial infarction (STEMI) treated with the primary percutaneous coronary intervention (PCI).Methods: One hundred one patients with STEMI, who underwent primary PCI were included in our study. Sixty-eight of these patients were randomized to the CR group and the remaining 33 patients to the control group. One month after the primary PCI, cardiac rehabilitation was performed in CR group with a cycle ergometer for 8 weeks (30 sessions). One month after STEMI, rhythm Holter monitorization was carried out in both groups for 48 hours. The rhythm Holter monitorization was repeated in cardiac rehabilitation group (CR group) after the cardiac rehabilitation again for 48 hours. HRV was evaluated according to time and frequency domains; HRT was evaluated with the turbulence onset and turbulence slope parameters obtained from the Holter recordings.Results: Baseline characteristics and baseline HRV and HRT parameters were comparable between CR group and control group. In CR group, there was no statistically significant difference between the HRV and HRT parameters, which were obtained before and after the cardiac rehabilitation. The subgroup analyses (left ventricular ejection fraction lower or higher than 40%) showed that turbulence onset improved with the cardiac rehabilitation in the group with an ejection fraction lower than 40%. Conclusions: Our results showed that exercise-based cardiac rehabilitation did not affect HRV and HRT in patients whose left ventricular ejection fraction was mildly affected (> 40%) after the treatment with primary PCI. However, the cardiac rehabilitation provided an improvement of turbulence onset in patients with the low left ventricular ejection fraction.